1999
DOI: 10.1074/jbc.274.22.15678
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biochemical Evaluation of the Interaction of the Phosphatidylinositol 3-Kinase p85α Src Homology 2 Domains with Phosphoinositides and Inositol Polyphosphates

Abstract: Src homology 2 (SH2) domains exist in many intracellular proteins and have well characterized roles in signal transduction. SH2 domains bind to phosphotyrosine (Tyr(P))-containing proteins. Although tyrosine phosphorylation is essential for protein-SH2 domain interactions, the binding specificity also derives from sequences C-terminal to the Tyr(P) residue. The high affinity and specificity of this interaction is critical for precluding aberrant cross-talk between signaling pathways. The p85␣ subunit of phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…It has been proposed that PIP 3 binds selectively to the p85 Cterminal (CT-)SH2 domain of PI3K, thereby blocking the binding of p85 to tyrosine-phosphorylated proteins (3). This model, however, was refuted by a recent NMR study that showed lack of specific binding of PIP 3 to p85 SH2 domains (13). Nevertheless, this question remains outstanding, because different structural analogues of PIP 3 were used as binding ligands in these investigations, i.e.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…It has been proposed that PIP 3 binds selectively to the p85 Cterminal (CT-)SH2 domain of PI3K, thereby blocking the binding of p85 to tyrosine-phosphorylated proteins (3). This model, however, was refuted by a recent NMR study that showed lack of specific binding of PIP 3 to p85 SH2 domains (13). Nevertheless, this question remains outstanding, because different structural analogues of PIP 3 were used as binding ligands in these investigations, i.e.…”
mentioning
confidence: 83%
“…Conceivably, understanding the mode of this unique phosphoinositide recognition will shed light on the mechanism by which PI3K regulates downstream signaling pathways. Although recent investigations demonstrate that distinct PH domains have evolved selectivity for different phosphoinositides to provide discriminatory regulation (5), data pertaining to the interactions between SH2 domains and PIP 3 are conflicting (3,13). It has been proposed that PIP 3 binds selectively to the p85 Cterminal (CT-)SH2 domain of PI3K, thereby blocking the binding of p85 to tyrosine-phosphorylated proteins (3).…”
mentioning
confidence: 99%
“…PI3K Assay-PI3K enzymatic activity was assayed as described previously by (49). HFKs were suspended, or adherent on immobilized anti-␣ 2 (P1H5), anti-␣ 3 (P1B5), or anti-␣ 6 (G0H3) integrin antibodies for 1 h, then extracted 1% v/v Nonidet P-40 detergent in kinase buffer (100 mM NaCl, 20 mM Tris-HCl, pH 7.4, 5 mM EDTA, 0.1 mM sodium orthovanadate, 20 mM MgCl 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The ligand-binding specificity arises mainly from the nature of the ␤D5 residue and pY ϩ 1 and pY ϩ 3 binding pockets (26,34). The second-messenger phosphoinositides produced by phosphoinositide 3-OH kinase have also been shown to bind to SH2 domains (35), although the physiological significance of this interaction has been disputed recently (36).…”
mentioning
confidence: 99%